The Influence of Learning-Oriented Organizational Culture on Innovation and Firm Performance in The Creative Industry - Herman Oddyansyah Felani; Ardhyanto Budirachman; Sarfilianty Anggiani (Eduvest - Journal of Universal Studies, 2024)
The creative industry is an important sector in the Indonesian economy. This industry has great potential to increase economic growth, job creation and national competitiveness. However, to achieve this potential, companies in the creative industries need to continue to innovate and improve their performance. One of the factors that can encourage innovation and company performance is a learning-oriented organizational culture. This research aims to analyze the influence of learning-oriented organizational culture on innovation in creative industry companies. This research uses quantitative research methods. Data was collected through surveys using questionnaires and literature studies. The data that has been collected is then analyzed using a regression test using the SPSS program. The research results show that a learning-oriented organizational culture has a positive influence on innovation and company performance in the creative industries. This culture creates an environment that encourages employees to continuously learn and develop, facilitates the exchange of ideas, and adopts new approaches to their work. In addition, a learning-oriented culture also improves overall company performance by improving operational efficiency, increasing employee satisfaction, and producing better and more innovative products or services.